Staging family : domestic deceptions of mid-nineteenth-century American actresses - Mullenneaux, Nan (Expanding frontiers., 2018)
"Examing the careers and lives of more than fifty nineteenth-century American actresses, Staging Family explores the interplay of culture, labor, and family in the advancement of mid-1800s social and political change"--